THE "NEW" DRUG CLASSES IN THE TREATMENT OF CHRONIC HEART FAILURE AND THEIR EVIDENCE BASE - S. N. Tereshchenko; I. V. Zhirov; A. G. Kochetov; O. V. Uspenskaya (Рациональная фармакотерапия в кардиологии, 2015)
A comparison of ivabradine and omega-3 polyunsaturated fatty acids, drugs with principally different mechanisms of action, is presented in patients with chronic heart failure (CHF) on the base of GISSI-HF and SHIFT trails results. It is essential to compaire an effect of these drugs on the morbidity and mortality in combined therapy of patients with CHF , because each additional drug may change in compliance to treatment, induces additional costs or may be a reason of new side effects. Additional (to standard therapy) effects of ivabradine and omega-3 polyunsaturated fatty acids are discussed.